Artificial intelligence based identification of the functional role of hirudin in diabetic erectile dysfunction treatment. (January 2021) - Yang, Ruocong; Liu, Chao; Li, Qianqian; Wang, Weilu; Wu, Bingbing; Chen, Aiping; Wang, Bin; Li, Wei; Chen, Jianxin
Graphical abstract: Highlights: An artificial intelligence-based strategy was used to identify new target of hirudin in diabetic erectile dysfunction treatment. Hirudin directly interacts with myeloperoxidase (MPO) and inhibits its activity. The inhibition of MPO decreases advanced glycation end products, preventing aging, thus ameliorates diabetic erectile dysfunction. Abstract: Diabetic erectile dysfunction (DED) hugely affected the patients' sexual life quality. However, there are no satisfactory therapeutic methods and intervention targets for this subtype of erectile dysfunction (ED). Inspired by the clinical practice of traditional Chinese medicine (TCM), we found that hirudin, the main active ingredient in the leech, could ameliorate the ED symptoms of the DED mouse model. To further reveal the underlying mechanism of hirudin, we designed a novel strategy to discover potential targets based on the diagnostic system of TCM, and found that myeloperoxidase (MPO) was a promising target of hirudin. Hirudin directly interacts with MPO and inhibits its activity, thus further decreases the content of oxidized low-density lipoprotein (ox-LDL) in serum. Our results demonstrated that the hirudin could ameliorate the symptoms of DED, and revealed the underlying mechanism of hirudin in regulating the activity of MPO.